Beyond the Sensorimotor Plasticity: Cognitive Expansion of Prism Adaptation in Healthy Individuals - Michel, Carine (Frontiers in Psychology, 2016)
Sensorimotor plasticity allows us to maintain an efficient motor behavior in reaction to environmental changes. One of the classical models for the study of sensorimotor plasticity is prism adaptation. It consists of pointing to visual targets while wearing prismatic lenses that shift the visual field laterally. The conditions of the development of the plasticity and the sensorimotor after-effects have been extensively studied for more than a century. However, the interest taken in this phenomenon was considerably increased since the demonstration of neglect rehabilitation following prism adaptation by Rossetti and his colleagues in 1998. Mirror effects, i.e. simulation of neglect in healthy individuals, were observed for the first time by Colent and collaborators in 2000. The present review focuses on the expansion of prism adaptation to cognitive functions in healthy individuals during the last 15 years. Cognitive after-effects have been shown in numerous tasks even in those that are not intrinsically spatial in nature. Altogether, these results suggest the existence of a strong link between low-level sensorimotor plasticity and high-level cognitive functions and raise important questions about the mechanisms involved in producing unexpected cognitive effects following prism adaptation. Implications for the functional mechanisms and neuroanatomical network of prism adaptation are discussed to explain how sensorimotor plasticity may affect cognitive processes.